Disfemia dalam Kolom Komentar Akun Youtube Najwa Shihab - Farida, Indri Nur; Darma Laksana, I Ketut; Putrayasa, I Gusti Ngurah Ketut (Stilistika : Journal of Indonesian Language and Literature, 2022)
This article examines the use of dysphemia in the comments column of Najwa Shihab's youtube account "Reformation Test". The comment column is a virtual interaction space for netizens. Every netizen can comment in the public space freely. Freedom to comment in the next section leads to the use of dysphemia. Dysphemia is an effort to replace words that mean smooth or ordinary with words that mean rude. There are two problem formulations in this article. 1) what is the form of dysphemia in the comment column of Najwa Shihab's youtube account "Reformation Test" 2) what are the characteristics of hate speech in the column Comments on Najwa Shihab's youtube account "Reformation Test" in terms of the use of dysphemia. The theory used is semantic theory, especially dysphemia. Data collection is carried out by the listening method, free to engage in conversation. Data analysis is carried out using the agih method with the determining element sorting technique (PUP). Presentation analysis results are presented informally and formally. The results of the 70 data showed that the use of dysphemia was dominated by the word form with 36 data. Dysphemia in the form of 26 data phrases, then 2 data in the form of clause dysphemia. The last 6 data form of sentence dysphemia. The existence of this form of dysphemia is intended to sharpen and strengthen the meaning in the commentary aspect. The characteristics of hate speech in the comments column of Najwa Shihab's youtube account "Reformation Test" in terms of the use of dysphemia are divided into four characteristics, namely insults, defamation, provocation, and unpleasant actions.